(untitled) (Research, Society and Development, 2022)
Among the actions of the clinical pharmacist is the optimization of the pharmacological treatment proposed to the patient, which consists of measures that aim to ensure a necessary, safe and effective pharmacotherapy. Objective: This work aims to report the activities of a pharmacist resident in the first year of the Residency Specialization Program in Adult and Elderly Health. Metodology: It is descriptive study type report of experience and has been made between August 2020 and January 2021. During the clinical pharmacy practice, in the medications review, it was observed that two injectable drugs presented nonconformities in terms of volume and type of diluent. This situation was observed by consulting available databases. Results and Discussion: In view of this, interventions were carried out with the hospital’s pharmacy management to adapt the information on drug prescriptions in the electronic drug distribution system and communication to the hospital’s servers through institutional dissemination. In addition, interventions were carried out with the nursing, medical and assistance teams to guide on the importance of the measures adopted for patient safety. Conclusion: In view of the above, the importance of the clinical pharmacist for the promotion and protection of the health of the hospital user is notorious.